Studies on Growth, Productivity and Economics of Oats Fodder as Influenced by Different Levels of NPK Fertilizers and Foliar Spray of ZnSO4 and Borax in Red and Lateritic Soil of West Bengal - Jaiswal, Divya; Mishra, S.; Yadav, K. N.; Akhil, K.; Barik, A. K.; Jaiswal, D. K.; Singh, Shubhi (International Journal of Bio-resource and Stress Management, 2024)
A field experiment was carried out during November–January, 2020–21 and 2021–22 at Institute of Agriculture, Visva–Bharati, Sriniketan, West Bengal to evaluate the response of NPK fertilizers and foliar application of ZnSO4 and borax towards growth, yield attributes, productivity and economic return from fodder oats cultivation. The experiment was laid out in factorial randomized block design having four levels of NPK fertilizers (viz., no fertilizer, 60:30:30, 80:40:40 and 100:50:50 kg ha-1) and three foliar spray [(viz., no foliar spray/water spray, ZnSO4 at 0.5%, borax at 0.2% and ZnSO4 + borax at (0.5% + 0.2%)] with three replications. Experimental findings revealed that NPK fertilizers with 100:50:50 kg ha-1 registered highest growth attributes, green fodder (36.46 t ha-1), dry fodder (9.18 t ha-1), gross return (₹54,685 ha-1), net return (₹25,681 ha-1) and return per rupee invested (1.89). Foliar spray of ZnSO4 + borax was significantly superior to sole application of borax and ZnSO4 with respect to growth attributes, green fodder (28.54 t ha-1), dry fodder (6.37 t ha-1), gross return (₹42,812 ha-1), net return (₹15,517 ha-1) and return per rupee investment (1.54) in oats. Thus, NPK fertilizers at 100:50:50 kg ha-1 and combined foliar spray of ZnSO4 and borax appeared to be the best option for higher fodder yield and profitability of fodder oats.